Engineering erucic acid biosynthesis in camelina (Camelina sativa) via FAE1 gene cloning and antisense technology: Control of erucic biosynthesis in Camelina - Bashiri, Hoda; Kahrizi, Danial; Salmanian, Ali Hatef; Rahnama, Hassan; Azadi, Pejman (Cellular and Molecular Biology, 2024)
Oil seeds now make up the world's second-largest food source after cereals. In recent years, the medicinal- oil plant Camelina sativa has attracted much attention for its high levels of unsaturated fatty acids and low levels of saturated fatty acids as well as its resistance to abiotic stresses. Improvement of oil quality is considered an important trait in this plant. Erucic acid is one of the fatty acids affecting the quality of camelina oil. Altering the fatty acid composition in camelina oil through genetic manipulation requires the identification, isolation, and cloning of genes involved in fatty acid biosynthesis. The Fatty Acid Elongase 1 (FAE1) gene encodes the enzyme β-ketoacyl CoA synthase (KCS), a crucial enzyme in the biosynthesis of erucic acid. In this study, the isolation and cloning of the FAE1 gene from Camelina sativa were conducted to construct an antisense structure. The molecular homology modeling of DFAE1 proteins using the SWISS-MODEL server on ExPASy led to the generation of the 3D structures of FAE1 and DFAE1 proteins. The GMQE values of 0.44 for FAE1 and 0.08 for DFAE1 suggest high accuracy in the structural estimation of these genes. The fragments were isolated from the DNA source of the genomic Soheil cultivar with an erucic acid content of about 3% (in matured seeds) using PCR. After cloning the FAE1 gene into the Bluescript II SK+ vector and sequencing, the resulting fragments were utilized to construct the antisense structure in the pBI121 plant expression vector. The approved antisense structure was introduced into the Camelina plant using the Agrobacterium-mediated method, with optimization of tissue culture and gene transfer conditions. This approach holds potential to advance our knowledge of fat biosynthesis, leading to potential improvements in oil quality in Camelina sativa.